Development of a temperature‐responsive yeast cell factory using engineered Gal4 as a protein switch. Issue 5 (24th January 2018) - Zhou, Pingping; Xie, Wenping; Yao, Zhen; Zhu, Yongqiang; Ye, Lidan; Yu, Hongwei
Abstract: Conflict between cell growth and product accumulation is frequently encountered in biosynthesis of secondary metabolites. Herein, a temperature‐dependent dynamic control strategy was developed by modifying the GAL regulation system to facilitate two‐stage fermentation in yeast. A temperature‐sensitive Gal4 mutant Gal4M9 was created by directed evolution, and used as a protein switch in Δ GAL80 yeast. After EGFP‐reported validation of its temperature‐responsive induction capability, the sensitivity and stringency of this system in multi‐gene pathway regulation was tested, using lycopene as an example product. When Gal4M9 was used to control the expression of P GAL ‐driven pathway genes, growth and production was successfully decoupled upon temperature shift during fermentation, accumulating 44% higher biomass and 177% more lycopene than the control strain with wild‐type Gal4. This is the first example of adopting temperature as an input signal for metabolic pathway regulation in yeast cell factories. Abstract : This work presents a temperature‐dependent dynamic control strategy for yeast developed based on directed evolution of the transcriptional activator Gal4, which facilitates decoupling of cell growth and product accumulation in fermentation of secondary metabolites, exemplified by lycopene, and may provide a viable approach to biosynthesis of heterologous proteins or metabolites that are toxic to the host cells.